Effects of Gestational Diabetes Mellitus on Fetal Cardiac Morphology - Esra Söylemez; Sermet Sağol (Medical Sciences)
Objective: This study aims to investigate the possible effects of gestational diabetes mellitus (GDM) on fetal heart structure and the relationship of this effect with maternal blood sugar control. Materials and Methods: In this cross-sectional study, 19 women with GDM at 24–36 weeks of gestation (case group) and 21 healthy pregnant women at the same weeks of gestation (control group) were examined. Fetal heart structure was evaluated by ultrasonography; interventricular septum (IVS) thickness, right and left ventricular sphericity indices, global sphericity index (GSI) and cardio-thoracic ratio were also measured. In addition, mothers’ HbA1c values (an indicator of blood sugar control) were recorded. Result: An increase in IVS thickness was observed in the fetuses of mothers with GDM. A more rounded trend was observed in the right ventricular structure, but this did not create a significant difference. No significant relationship was found between maternal blood sugar control and fetal heart structure. Conclusions: This study examined the effects of gestational diabetes on fetal cardiac morphology and the relationship of this effect with maternal glycemic control. Babies of mothers with GDM had a significantly thicker interventricular septum. A more rounded trend was detected in the right ventricular structure. However, this change was not found to be statistically significant. In addition, no significant correlation was found between maternal glycemic control and fetal cardiac morphology.